Therapeutic Effects of Natural Drugs on Alzheimer’s Disease - Ma, Yuan; Yang, Man-wen; Li, Xin-wei; Yue, Jian-wei; Chen, Jun-zong; Yang, Mei-wen; Huang, Xuan; Zhu, Lian-lian; Hong, Fen-fang; Yang, Shu-long (Frontiers in Pharmacology, 2019)
Alzheimer disease (AD) is characterised as a kind of chronic neurodegenerative disease which is associated with age. And its clinical manifestations are composed of latent episodes of memory and cognitive impairment, psychiatric symptoms and behavioral disorders as well as limited activities in daily life. In the developed countries, AD is now acknowledged as the third leading reason of death, only second to the cardiovascular disease and cancer. The pathogenesis and mechanism of AD are still unclear now, although there are already some theories to explore AD, such as β-amyloid theory, the theory of abnormal metabolism of tau protein, the theory of free radical damage, the theory of inflammatory response and cholinergic damage theory and etc. There are still no effective ways to predict, prevent or reverse AD, so developing new efficient therapeutic drug becomes a global hot spot currently. Isolating and extracting active component from natural drug has great potential in treating AD, which presents the advantages of multiple target point, multi-pathway, less side effects and long duration of curative effect. This essay summaries the latest research progresses of natural drug mechanisms in the treatment of AD, providing literature and theoretical basis for better clinical treatment of AD.